HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG FAKTOR RESIKO ASFIKSIA PADA NEOANTUS DENGAN PERENCANAAN RUJUKAN PERSALINAN - Wan Anita; Lita Nafratilova; Ayu Sri Pratiwi; Susi Susanti; Devi Septiani (JOMIS (Journal of Midwifery Science), 2022)
Asphyxia is a condition in which the baby cannot breathe, thus reducing O2 and increasing CO2 which is bad. Risk factors for the incidence of asphyxia are maternal factors such as his disorder, presence of antepartum bleeding, maternal age less than 20 years or more than 35 years, primiparous and grande multiparous, low socioeconomic, preeclampsia and his disorders. Infant factors, namely respiratory depression due to anesthesia or analgesic drugs given to the mother, intracranial bleeding, congenital abnormalities, premature, postmature, location abnormalities, twins, shoulder dystocia, vacuum extraction, forceps, amniotic fluid mixed with meconium. Placental factors include umbilical cord twisting, short umbilical cord, umbilical cord knot, and umbilical cord prolapse. The purpose of this study was to determine the relationship between knowledge of pregnant women about risk factors for newborn asphyxia with delivery referral planning. This type of research is quantitative analytic with a cross sectional research design. This research was conducted at Puskesmas RI Sidomulyo with a research instrument in the form of a questionnaire. The results showed a relationship between mother's knowledge of risk factors for newborn asphyxia and delivery referral planning with p value = 0.007. This study is expected for midwives in providing midwifery services to pregnant women to provide knowledge about the risk factors for newborn asphyxia so that pregnant women can make a labor referral plan if during the delivery process they experience the risk of newborn asphyxia and the knowledge of pregnant women about risk factors for infant asphyxia. newborns so that they can plan a delivery referral if an emergency case is found in a newborn.